(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The quenching of the photoinduced excited triplet of 9,10-anthraquinone (^3AQ^*) by Vitamin C (VC) has been studied in ethylene glycol-water (EG-H_2O, EG/H_2O=9/1, v/v) homogeneous by using time-resolved electronic paramagnetic resonance (TR-EPR) and laser flash photolysis techniques. According to the chemically induced dynamic electron polarization (CIDEP) and transient absorptive spectra, the reaction intermediates and the reaction mechanism have been analyzed. The rate constant for the quenching of excited triplet ^3AQ^* by VC has been measured. The results indicate that ^3AQ^* can capture hydrogen atom not only from ethylene glycol molecule but also from VC. The strong CIDEP signal of VC monoanion radical indicates that the quenching of VC to ^3AQ^* is obvious. The rate for the quenching of ^3AQ^* by VC is nearly diffusion-controlled.